Study of Deep Water Needs For the Development of Irrigation Network in Sigulai Village, Simeulue Regency - Hani Fadlina; Dian Febrianti; Zulyaden Zulyaden (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2023)
The irrigation area in Sigulai Village is a rain-fed rice field whose irrigation water depends on rainwater and mountains. So that during the dry season, the rice fields cannot be planted due to a lack of water availability. The purpose of this analysis is to determine the need for deep water for the construction of irrigation networks, the capacity of the pumps used and to analyze the rotation of the water supply to each paddy field. The results showed that the irrigation network in Sigulai Village, Simeulue Regency had 1 water pump to irrigate the rice fields. The irrigated rice fields are located on the back (back) of the technical irrigation network in Sigulai Village, Simeulue Regency, so that even though there is a technical irrigation network, irrigation water has not been able to reach all of the rice fields because the rice field elevation is higher than the canal elevation. The amount of water needed for one harvest is 22,809,600 M3/one harvest for a paddy field area of 42 Ha (rice, horticulture, crops). The time required for pump operation to irrigate 42 hectares of rice fields is 23 hours 45 minutes/day with a pump capacity of 8000 (ltr/hour)